Audit Review: Managers' Interpersonal Expectations and Conduct of the Review* - Gibbins, Michael; Trotman, Ken T. (Contemporary Accounting Research, 2002)
Abstract This paper presents an interpersonal model of audit file review centered on the audit manager. A manager's conduct of the review is affected by four components: the manager's expectations about the client, expectations about the preparer, expectations about the partner, and the manager's own approach and circumstances. The paper then presents a comprehensive field‐based analysis of how a working paper review is conducted. It supplements the mostly experimental research on working paper review by reporting the results of a retrospective field questionnaire that asked audit managers to report on their behavior and their relationships with preparers and partners on actual audit engagements. The extent of review was sensitive to specific features of the client and the file (including risk factors), to features of the preparer, and particularly to the style of the reviewer, which was quite stable across cases. Although the evidence of managers' awareness of preparers' “stylizing” the file to suit the manager was weak, the evidence of managers' stylizing for the partners was pervasive, affecting both work done and documentation. Managers believed that good reviews emphasized key issues and risks rather than detail. Other new descriptive evidence on the nature of the review process is provided, including the purpose of the review process, how frequently surprises are found in the review process, and the qualities of good reviewers compared with poor reviewers. The implications of our model and our results for future research are outlined.